Konseling Kelompok Berbasis Behavioral sebagai Strategi Modifikasi dan Penguatan Perilaku Positif - Rahmatul Ulfa Aulia; Neviyarni Neviyarni; Netrawati Netrawati; Rezki Hariko (Empowerment Counseling Journal, 2025)
Group counseling is one of the core services in guidance and counseling designed to help individuals gain self-understanding, develop their potential, and cope with various personal, social, and academic challenges. One effective approach in conducting group counseling is the behavioral approach. This approach is grounded in the principle that human behavior is shaped through learning processes; therefore, maladaptive behaviors can be modified into more positive ones through practice and reinforcement. In its implementation, the behavioral approach employs several techniques such as reinforcement, modeling, role playing, behavior rehearsal, and systematic desensitization. Through group dynamics, individuals learn to imitate constructive behaviors, receive feedback from peers, and establish new habits that support psychological well-being. Thus, behavioral-based group counseling serves not only as a therapeutic medium but also as an effective social learning environment that fosters discipline, responsibility, and adaptive behavior among participants. Keywords: behavioral approach, learning process, positive behavior, social learning, psychological well-being